A novel photoresponsive benzoquinolone: evaluation of the release of model amino acids - Soares, Ana M. S. (2015)
A photoresponsive benzoquinolone was conjugated with two model amino acids at their C-terminus, affording the corresponding ester conjugates. These ester conjugates were submitted to photocleavage studies in different mixtures of methanol/HEPES buffer solution at different wavelengths of irradiation (300, 350 and 419 nm), which confirmed the quantitative release of the model molecules in short irradiation times.